Framing consciousness in art : transcultural perspectives - Minissale, Gregory (Consciousness, literature & and the arts ;, 2009)
Framing Consciousness in Art shows how the frames-in-frames in these different contexts question notions of vision and representation, linear time, conventional spatial coordinates, binaries of 'internal' consciousness and 'external' world, subject and object, and the precise anatomy of mental states by which we are meant to carve up the territory of consciousness. The phenomenological experience of art is certainly as important as the folk psychology which scientists and philosophers use to taxonomise ordinary first-person modes of subjectivity. Yet art excels in configuring the visual field.